Development of the ALFRED reactor full power mode control system. (November 2015) - Ponciroli, Roberto; Cammi, Antonio; Della Bona, Alessandro; Lorenzi, Stefano; Luzzi, Lelio
Abstract: In this paper, the full power mode control scheme for the pool-type Advanced Lead Fast Reactor European Demonstrator (ALFRED) is presented. The design process of a nuclear power plant control system is a multi-step process, whose final result is the implementation of the feedback controllers. In particular, the control system configuration has been finalized after having considered different strategies to govern the variables of interest (e.g., power produced in the core, coolant temperature, pressure, etc.). In a previous work (Ponciroli et al., 2014b), the most relevant issues regarding both the controlled outputs (e.g., the lead temperature in the cold leg) and the control inputs (e.g., the feedwater inlet temperature and the lead mass flow rate) have been allowed for. Based on these preliminary analyses, the control strategy has been further developed, and the full power mode control scheme for the ALFRED reactor has been implemented. As a major outcome, it has been demonstrated how a decentralized control scheme based on a battery of PI controllers allows obtaining satisfactory performance. Indeed, starting from the linearization of the dedicated object-oriented model, the level of decoupling among the control loops has been verified, confirming the validity of the proposed solution based on the outcomes of the Relative Gain Array (RGA) method. This result has been achieved thanks to a proper tuning of the controller parameters, which allows damping the undesired influence due to the other control loops. Finally, as for the design of the actuators, a quantitative approach based on the outcomes of the system linear stability analysis has been proposed, in order to define the maximum safety value for the extraction speed of the control rods. Highlights: Object-Oriented modelling for the development of a control-oriented simulator of the ALFRED reactor. Development of an effective control strategy according to the RGA-based analysis. Verification of the mutual level of interaction among the control loops in a decentralized control scheme. Quantitative procedure to set the maximum safety value for the control rod extraction speed.